Escala de ansiedade odontológica: Reprodutibilidade das respostas dadas em entrevistas telefônicas e pessoais - Presoto, Cristina Dupim [UNESP]; Cioffi, Sabrina Spinelli [UNESP]; Dias, Tiago Mendonça [UNESP]; Loffredo, Leonor de Castro Monteiro [UNESP]; Campos, Juliana Alvares Duarte Bonini [UNESP] (APESB (Associacao de Apoio a Pesquisa em Saude Bucal), 2011)
Objective: To estimate the intra-examiner reproducibility of the Dental Anxiety Scale (DAS) when applied by phone and personal interviews and to evaluate the association between the level of anxiety and the factors of interest. Method: The participants were 50 individuals (n=38 females) with mean age of 23.9±8.9 years, living in the city of Araraquara, SP, Brazil. The volunteers answered the DAS by means of two phone interviews with one-week interval between them. After 30 days, the DAS was applied to the same participants by means of personal interviews at two moments with one-week interval between them. Intra-examiner reproducibility was determined using Kappa (K) statistics by point and by confidence interval. Results: The intra-examiner agreement for the level of anxiety was 0.82 (0.75-0.90) for the phone interview and 0.69 (0.60-0.79) for the personal interview. Two of the DAS questions presented statistically significant difference in the intra-examiner reproducibility, with better agreement for the answers given by the participants during phone calls. The prevalence of dental anxiety in the sample was 92.0%, in such a way that 70.0%, 18.0% and 4.0% of them presented low, moderate and exacerbated anxiety. Conclusion: The classification of the individuals according to the anxiety level performed by means of phone and personal interviews presented statistically similar agreement. However, there was better agreement with phone calls for the questions referring to anxiety in the dental office's waiting room and during preparation of the motor for use in the dental treatment.
Dental anxiety scale: Reproducibility of answers given in phone and personal interviews
Keywords: Anxiety; Community dentistry; Interview